Collection Care: Environmental Monitoring, Risk Assessment and Risk Management (Springer Proceedings in Archaeology and Heritage, 2025)
This open access book compiles the contributions of the conference Collection Care: New Challenges in Environmental Monitoring, Risk Assessment and Risk Management. The conference held within the framework of the EU’s Horizon2020 CollectionCare project (grant no. 814624), was a forum where the latest technological advances in the study of the behavior and aging of cultural heritage materials, environmental monitoring, and the design of preventive conservation strategies in collections were presented. This volume is of interest to heritage researchers and is divided into two sections: the first brings together thirteeen papers that focus on the monitoring, analysis, data interpretation and modelling of the effects of different degradation agents (temperature, relative humidity, pollutants, light, vibration, etc.) in materials present in cultural heritage objects. The second part of the book presents eight case studies dealing with risk assessment and risk management in different types of collections with diverse needs, priorities, and resources, thus illustrating the complexity of implementing all the current knowledge on sensing, monitoring, predictive analysis and preventive conservation in the design of conservation strategies. The case studies presented also demonstrate how these tools have contributed to maximise dialogue and coordination between the different stakeholders involved in the conservation of cultural heritage.